Educational Foundations and the Values of Global Pedagogy - Gordon, Richard K. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol 68 (2010))
Educational Foundations offers insight into the value societies hold for educating youth. Examining global perspectives concerning the societal desire for education using the phenomenological idea of the Other leads to understanding the educative experience as a normative feature of teaching and learning. By communicating this normative feature with the theoretical notion of the “Golden Circle,” educators develop a strong qualitative foundation for theorizing and interpreting results of quantitative educational research.
Keywords: normative, educative experience, the Other, Golden Circle